Nociceptive and sympathetic innervations in the abaxial part of the cranial horn of the equine medial meniscus: an immunohistochemical approach. Issue 6 (27th June 2016) - Nemery, Elodie; Gabriel, Annick; Piret, Joëlle; Antoine, Nadine
Abstract: In athletic horses, diseases leading to lameness are of great importance due to the loss of performance and the resultant economic concerns. Although stifle lesions are frequent in the hindlimb, due to the large size and complexity of the joint, and although meniscal tears have been identified as the most common soft tissue injuries in this joint, little is known about the mechanism that causes the painful sensation and thus the lameness. The aim of our study was to highlight any peripheral fibres involved in meniscal nociception in five macroscopically sound cranial horns of the equine medial meniscus, which has been one of the most common sites reported for equine meniscal injuries. Immunohistochemical stainings were performed using antibodies against Substance P in order to identify nociceptive fibres; against tyrosine hydroxylase for detecting postganglionic sympathetic fibres; and against glial fibrillary acidic proteins in order to identify Schwann cells. Our work highlights for the first time the presence of nociceptive and sympathetic fibres in equine menisci. They were found in the abaxial part of the cranial horn of the equine medial meniscus. This study suggests that when the abaxial part is injured, the meniscus itself could be the source of pain. These findings could provide a better understanding of the clinical presentation of horses with meniscal injury and contribute towards improving therapeutic strategies to alleviate pain in cases of equine meniscal injury.